Elucidating the magmatic history of the Austurhorn silicic intrusive complex (southeast Iceland) using zircon elemental and isotopic geochemistry and geochronology - Padilla, Abraham J.; Miller, C. F.; Carley, T. L.; Economos, R. C.; Schmitt, Axel Karl; Coble, M. A.; Wooden, J. L.; Fisher, C. M.; Vervoort, J. D.; Hanchar, J. M. (Contributions to mineralogy and petrology, 2016)
The Austurhorn intrusive complex (AIC) in southeast Iceland comprises large bodies of granophyre and gabbro, and a mafic-silicic composite zone (MSCZ) that exemplifies magmatic interactions common in Icelandic silicic systems. Despite being one of Iceland’s best-studied intrusions, few studies have included detailed analyses of zircon, a mineral widely recognized as a valuable tracer of the history and evolution of its parental magma(s). In this study, we employ high spatial resolution zircon elemental and isotopic geochemistry and U-Pb geochronology as tools for elucidating the complex construction and magmatic evolution of Austurhorn’s MSCZ. The trace element compositions of AIC zircon crystals form a broad but coherent array that partly overlaps with the geochemical signature for zircons from Icelandic silicic volcanic rocks. Typical of Icelandic zircons, Hf concentrations are relatively low (<10,000 ppm) and Ti concentrations range from 5 to 40 ppm (Ti-in-zircon model temperatures = 761-981 °C). Zircon δ18O values vary from +2.2 to +4.8 ‰, consistent with magmatic zircons from other Icelandic silicic rocks, and preserve evidence for recycling of hydrothermally altered crust as a significant contribution to the generation of silicic magmas within the AIC. Zircon εHf values generally range from +11 to +15. This range overlaps with that of Icelandic basalts from off-rift settings as well as the least depleted rift basalts, suggesting that the AIC developed within a transitional rift environment. In situ zircon U-Pb ages yield a weighted mean of 6.52 ± 0.03 Ma for the entire complex, but span a range of ~320 kyr, from 6.35 ± 0.08 to 6.67 ± 0.06 Ma (2σ SE). Gabbros and the most silicic units make up the older part of this range, while granophyres and intermediate units make up the younger part of the complex, consistent with field relationships. We interpret the ~320 kyr range in zircon ages to represent the approximate timescale of magmatic construction of the MSCZ. These U-Pb data suggest that the complex was constructed by multiple short-lived magmatic intrusion events occurring closely spaced in time, allowing periodic re-melting and rejuvenation of mush-like material and a prolonged lifetime for the complex.
Gesehen am 23.10.2020